Bifid Uvula in three members of a family - Suwarna Dangore Khasbage (International Journal of Oral and Craniofacial Science - Peertechz Publications, 2017)
Uvula is a key organ in functions like speech, deglutition and mastication. The majority of the world population has a uvula that is conical in shape, hanging upside down. However, there are times when the uvula is split, the condition is called a bifi d or bifurcated uvula. Sometimes it is also called a cleft uvula. Three male blood relatives, father and his two sons reported to outpatient department of Oral Medicine and Radiology at Sharad Pawar Dental College, Wardha for odontogenic complaint. But, their intraoral examination revealed interesting fi nding, that was presence of bifi d uvula and cleft palate in three of them, who were of course fi rst relatives of each other. The presentation of the condition in three members of the same family is a unique feature of this article.